Idiopathic thoracic spinal cord herniation. (May 2018) - Ghali, Michael G.Z.; Srinivasan, Visish M.; Rao, Vikas Y.; Omeis, Ibrahim
Highlights: Spinal cord herniation (SCH) is uncommon. SCH is usually idiopathic and occurs in the thoracic cord. SCH presents as a subacute myelopathy. Operative repair is indicated for idiopathic spinal cord herniation. Abstract: Idiopathic spinal cord herniation represents an uncommon and unique diagnostic entity, most commonly affecting middle-aged individuals, with a nearly twofold female predilection. It most characteristically affects the mid-thoracic spine, with the herniation occurring ventrally or ventrolaterally. Clinical presentation is typically a slowly-progressive myelopathy, with Brown-Séquard syndrome occurring more frequently than spastic paraparesis. Diagnosis is made by imaging, with high-resolution or phase-contrast MR sequences and/or CT myelography. Treatment should be individualized, with options including conservative management with routine follow-up and surgical intervention. We review the literature on this interesting topic and report on, and present our technique for, operative reduction and repair of idiopathic spinal cord herniation in a 66 year-old woman.